PERANAN INSENTIF TERHADAP EFEKTIVITAS KERJA PEGAWAI DI UPT DINAS PENDIDIKAN KECAMATAN ANGGANA KABUPATEN KUTAI KARTANEGARA - Andini, Riyal (PREDIKSI, 2015)
ABSTRACTÂ The purpose of this study was to determine the effect of causation between the incentive to improve the effectiveness of employees working at the Department of Education's Office District of Anggana UPT KutaiKartanegara District. Therefore, we propose the hypothesis in this study as follows: "If an employee is the effectiveness of employee incentives tend to increase as well."Research conducted on employees through two variables, namely incentive as the independent variable and the effectiveness of employee as the dependent variable. To obtain the data used technique questionnaire submitted to 11 (eleven) employees.The study found rs-count (0.7021)> (0.618) rs-table, in other words there is a relationship between the effectiveness of employee incentives in kantorUPT Department of Education District of Anggana, Regency. Additionally rs> 0, there is a positive linear relationship. When the count value of rs-interpreted the strong correlation between the effectiveness of incentives to employees working in the office of the Department of Education District of Anggana UPT, Regency. T-test results obtained figures t-test = 4.1545 while the number of t-table at the significance level ï¡ = 0.025 for the test one-sided or two-sided 0.05 for the test is = 2.262. Thus H0 H1 accepted meaning ditolakdan proposed hypothesis is accepted, because there is significance (significance) between the effectiveness of incentives to employees in the office of the Department of Education District of Anggana UPT, Regency.